Determination of Optimal Acoustic Passive Reflectors to Reduce Bycatch of Odontocetes in Gillnets - Kratzer, Isabella M. F.; Schäfer, Ingo; Stoltenberg, Arne; Chladek, Jérôme C.; Kindt-Larsen, Lotte; Larsen, Finn; Stepputtis, Daniel (Frontiers in Marine Science, 2020)
The need to minimize bycatch of toothed whales (odontocetes) in gillnets has long been recognized, because they are often top predators and thus essential to ecosystem resilience. It is likely that a key to achieving this goal is the improvement of gillnet acoustic visibility, because these species use underwater sonar for orientation. Previous work on increasing gillnet detectability for echolocating animals by making the nets more recognizable has been based on trial and error, without understanding the fundamental acoustic properties of the tested modifications. Consequently, these studies have produced mixed and sometimes contradictory results. We systematically identified small, passive reflective objects that can improve the visibility of gillnets at a broad range of frequencies, i.e., for many odontocetes. We simulated the acoustic reflectivity of a wide range of materials in different shapes, sizes, and environmental conditions. We verified the simulation results experimentally and calculated detection distances of the selected modifications. For example, if 8mm acrylic glass spheres are attached to the net at intervals smaller than 0.5 m, the spheres have the same target strength (TS) at 130 kHz as the most recognizable part of a gillnet, the floatline. Modifications of the netting material itself, e.g., using barium sulfate additives, do not substantially increase the acoustic reflectivity of the net.